Spanish American Women Writers: Simmering Identity Over a Low Fire - Ksenija Bilbija (Studies in 20th & 21st Century Literature, 1996)
After establishing the parallel between the kitchen and the alchemist's laboratory, this article shows that traditionally, the kitchen has come to symbolize the space associated with the marginalization of women. However, the recent explosion of the novels dedicated to the resemantization and reevaluation of the realm of the kitchen is the best evidence that it is also a space from which much creativity emanates. A close reading of two such cookbook/novels, Like Water for Chocolate by Laura Esquivel and Like Potatoes for Varenike by Sylvia Plager, points toward a quite parodic and critical gender perspective. Furthermore, it calls for a reinterpretation of stereotypical power relations and of male and female identity symbols.
Keywords: Spanish American women writers; Cómo agua para chocolate; women writers; identity; kitchen; space; marginalization; creativity; Like Water for Chocolate; Laura Esquivel; Like Potatoes for Varenike; Sylvia Plager; gender; power relations; power; male; female